Intercrop yields of cassava and rice as influenced by cassava variety and population - Dahniya, Mohamed T.; Jalloh, A.; Ezumah, H.C. (International Society for Horticultural Science, 1994)
The cassava variety and population, which when intercropped with rice leads to increased productivity of the system were identified. Two cassava varieties (Cocoa, a local variety; and 80/40, an improved one) were each planted at four populations (6 666, 10 000, 13 333, and 16 666) as sole crops or intercropped with the rice variety Rok 16. Variety 80/40 significantly out yielded Cocoa (17.2 and 4.1 t/ha, respectively). There was no significant difference in yield between sole and intercropped cassava. Tuberous root yield significantly increased as population increased, with the highest yield (13.0 t/ha) obtained at 16 666 and the lowest (8.3 t/ha) at 6 666. Rice yield did not vary significantly with cassava variety. Increase in cassava population significantly depressed rice yield. All intercropping systems had LER values greater than one. Highest LER was obtained when rice was intercropped with cassava at 6 666 (1.85 for 80/40 and 1.73 for Cocoa). LER decreased as cassava population increased. Thus productivity of the cassava-rice intercropping system can be improved by increasing the cassava population up to 6 666 and by growing the improved variety 80/40.